Enhancement of Heat Transfer in Subcooled Pool Boiling by Nano-textured Surface - KNEITA, El Ghassem; HONDA, Takuro; KASAMURA, Keiji; NAKASHIMA, Yuta; KOITO, Yasushi; NAKANISHI, Yoshitaka (2018 7th International Conference on Renewable Energy Research and Applications (ICRERA), 2018)
Subcooled boiling on nano-textured surface was studied experimentally using ethanol as working fluid. The nano-textured surface presented in this study was copper plate, which was processed using a micro slurry-jet erosion machine, the corresponding surface had three dimensional waviness curves with 100 nm in depth and 1 mm in width. In addition for comparison, conventional copper flat plate was used as a control surface. Each surface was attached to a heat source, and heat was transferred by pure conduction from the heat source to the top of each surface. Furthermore, the heat flux was measured and calculated experimentally using Fourier law's for conduction. Our experimental results showed that during boiling, the heat flux on the nano-textured surface was higher than its counterpart on the conventional flat copper surface. This seems to be from the fact that the nano-textured surface facilitates bubble growth rate, which increase bubble detachment frequency from the heated surface. On the other hand, the nano-textured surface developed in the present work seems to be robust and cannot be detached from the surface or deteriorate since it is a part of the material. This property could be attractive for future industrial applications. However, the optimal texture is the subject for our further study.